Study of Deposition Time Influence the Conical Structure during Electron Beam Induced Deposition (EBID) - Mohamad Sharizal Md Ilias (Universiti Malaysia Perlis, 2008)
Atomic force microscopy (AFM) is now a well-established technique for the surface characterization and imaging of a variety of materials. In AFM the accuracy of data is often limited by the tip geometry and the effect on this geometry of wear. One way to improve the tip geometry is by fabricate a slim probe on tip of cantilever probe by vertical growth method. In this project, we used the electron beam induced deposition (EBID) method which is formed in scanning electron microscope (SEM). The material that we developed on the silicon wafer is a carbon. The influence of deposition time to the length, diameter and shape of the deposited structure has been studied and analyzed in this project. Deposition time from one to nine minutes and acceleration voltage between 21 kV to 24 kV has been used as the parameter. High potential of slim probe for AFM fabricated at Unimap’s Clean Room can be utilized for commercialization potential. Therefore further research and improvement of slim probe for AFM formation is crucial to further develop in semiconductor technology